2011
DOI: 10.15835/nbha3913455
|View full text |Cite
|
Sign up to set email alerts
|

HPLC Fingerprint of Bioactive Compounds and Antioxidant Activities of Viscum album from Different Host Trees

Abstract: Viscum album L. is a medicinal plants used for many years as a remedy in the traditional medicine and in complementary cancer therapies. We investigated the influence of some host trees: Acer campestre (VAA), Fraxinus excelsior (VAF), Populus nigra (VAP), Malus domestica (VAM), and Robinia pseudoacacia (VAR), on the chemical composition and antioxidant activity of leaves and stems from V. album, as well the influence of the solvent (water and ethanol) used for extraction on biological activity. HPLC with photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 29 publications
(24 reference statements)
4
54
1
Order By: Relevance
“…Plant flavonoids have antioxidant activity in vitro and also act as antioxidants in vivo [15]. Recently, Vicas et al [16]reported that the TFC of the ethanol extracts of mistletoe V. album harvested from six different hosts were 0.05-2.19 mg RE/100 g, which is 6.8-324 folds lower than that of the ethanol extract (14.9 mg RE/100 g) in our study (Table 1). This implies that differences of secondary metabolites in mistletoes are influenced by the kind of host plants and the type of solvents used for extraction.…”
Section: Phytochemical Contentsmentioning
confidence: 42%
“…Plant flavonoids have antioxidant activity in vitro and also act as antioxidants in vivo [15]. Recently, Vicas et al [16]reported that the TFC of the ethanol extracts of mistletoe V. album harvested from six different hosts were 0.05-2.19 mg RE/100 g, which is 6.8-324 folds lower than that of the ethanol extract (14.9 mg RE/100 g) in our study (Table 1). This implies that differences of secondary metabolites in mistletoes are influenced by the kind of host plants and the type of solvents used for extraction.…”
Section: Phytochemical Contentsmentioning
confidence: 42%
“…Also, like in mistletoe hosted by P. Table 1. Quantitative HPLC analysis of bioactive aglicones of phenolics (µg/g dry matter*) from leaves and stems of V. album harvested from different hosts, on July 2009 (Vicas et al,2011a).…”
Section: Hplc Fingerprint Of Bioactive Compounds From Viscum Albummentioning
confidence: 99%
“…4. HPLC chromatograms, used to fingerprint and evaluate quantitatively phenolic acids from leaves and stems of V.album harvested from Fraxinus excelsior (VAF) (Vicas et al, 2011a). 3 -protocatechuic acid 5 -chlorogenic acid 6 -para-OH benzoic acid 7 -cafeic acid 8 -syringic acid 9 -salicylic acid 10 -para-coumaric acid 11-ferulic acid 12 -sinapic acid www.intechopen.com…”
Section: Hplc Fingerprint Of Bioactive Compounds From Viscum Albummentioning
confidence: 99%
See 1 more Smart Citation
“…Other classes of secondary metabolites from Viscum album are flavonoids, phenylpropanoids, triterpenes, phytosterols, cyclic peptides and cyclitols [6]. Being a parasitic plant, the phenolic content and the antioxidant capacity of mistletoe have been found to vary depending upon the host trees and the time of harvest [9,10]. New compounds have been also reported in mistletoe growing on different hosts [11].…”
Section: Introductionmentioning
confidence: 99%